Construction and Preliminary Application of the Carbon-based Spatial Governance Performance Evaluation System ——Taking Zhejiang Province as an Example - Qu, Lin; Xia, Ganlin; Bao, Cunkuan, Prof. (UI Scholars Hub, 2023)
Carbon is generated through human socio-economic activities, with territorial space serving as the medium for these activities. Variations in spatial governance result in differences in the scale, intensity and efficiency of social and economic activities, as well as energy and resource consumption and carbon emissions across diverse functional spaces. Consequently, spatial governance performance should be evaluated using carbon-related indicators. This study initially established a theoretical model for assessing spatial governance performance based on carbon and an evaluation method encompassing three dimensions or indices